(untitled) (Economic and Political Thought, 2018)
The East Asian development model, as a result of which some Asian economies have achieved spectacular developmental results, is based on the concept of a developmental state. The developmental state is characterized by specific systemic and institutional arrangements. In principle, it functions in the conditions of the capitalist system (socialism is not able to generate adequate growth dynamics in the long term); nevertheless, the authorities apply central planning mechanisms to implement their development strategy. Thus, state interventionism plays an important developmental role, although it is not intended to ensure social cohesion.